SOSIALISASI PERAN ORANG TUA DALAM MEMBERIKAN PENDIDIKAN SEKS PADA ANAK USIA DINI - Miftahul Janah; Agustina Ekasari; Siti Khadijah (An-Nizam, 2022)
Cases of sexual harassment by those closest to them, including family, have increased. One reason is that children do not have knowledge that can make children anticipate sexual harassment. Based on these problems, sex education for their children is very important to reduce these problems. The purpose of this study was to determine the function and role of sex education for children in the family, issues of child growth and development towards sex education, and the role of parents in fostering sex education. The result of the implementation of community service related to the role of parents in sex education in early childhood is that parents already understand the meaning of sex education that really needs to be taught to their children from an early age as evidenced by the evaluation results through questions given by parents who also understand.